The coordination abilities development in female students based on dance exercises - Olga V. Limanskaya; Olena V. Yefimova; Irina V. Kriventsova; Krzysztof Wnorowski; Abdelkrim Bensbaa (Physical Education of Students)
Background and Study Aim. The physical fitness of students is characterized by the level of their abilities development to perform movements of varying complexity. One of the important components in the system of movements is coordination skills. The aim of the study is to identify the level of special and general coordination of students majoring in "Choreography" and provide recommendations for the development of coordination skills in the process of studying modern-jazz dance.